All‐Inorganic Perovskite Quantum‐Dot Optical Neuromorphic Synapses for Near‐Sensor Colored Image Recognition - Yung‐Chi Yao; Chia‐Jung Lee; Yong‐Jun Chen; Jun‐Zhi Feng; Hongseok Oh; Chin‐Shan Lue; Jinn‐Kong Sheu; Ya‐Ju Lee (Advanced Science)
Abstract As the demand for the neuromorphic vision system in image recognition experiences rapid growth, it is imperative to develop advanced architectures capable of processing perceived data proximal to sensory terminals. This approach aims to reduce data movement between sensory and computing units, minimizing the need for data transfer and conversion at the sensor‐processor interface. Here, an optical neuromorphic synaptic (ONS) device is demonstrated by homogeneously integrating optical‐sensing and synaptic functionalities into a unified material platform, constructed exclusively by all‐inorganic perovskite CsPbBr3 quantum dots (QDs). The dual functionality of each unit within the ONS device, which can be operated as either an optical sensor or a synaptic device depending on applied electrical polarity, provides significant advantages over previous heterogeneous integration methods, particularly regarding material selection, structural compatibility, and device fabrication complexity. The ONS device exhibits distinct wavelength responses essential for emulating colored image recognition capability inherent in the human visual system. Additionally, the seamless integration of electronics and photonics within a unified material system establishes a novel paradigm for optical retrieval, enabling real‐time perception of the encoded status of the ONS device. These findings represent substantial advancements in near‐sensor computing platforms and open a new horizon for all‐inorganic perovskite optoelectronic technologies.